2017
DOI: 10.3389/fpsyg.2017.01050
|View full text |Cite
|
Sign up to set email alerts
|

Joint Rhythmic Movement Increases 4-Year-Old Children’s Prosocial Sharing and Fairness Toward Peers

Abstract: The allocation of resources to a peer partner is a prosocial act that is of fundamental importance. Joint rhythmic movement, such as occurs during musical interaction, can induce positive social experiences, which may play a role in developing and enhancing young children’s prosocial skills. Here, we investigated whether joint rhythmic movement, free of musical context, increases 4-year-olds’ sharing and sense of fairness in a resource allocation task involving peers. We developed a precise procedure for admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
1
36
0
1
Order By: Relevance
“…Less activation anterior parietal fMRI 7−10, n = 21 Nishimura et al, 2018 Action observation Mu suppression during observation weaker than in adults and less in allocentric compared to egocentric configuration EEG 8−12, n = 28 Nobusako et al, 2018 Automatic imitation Effect of congruency on trajectory when drawing on tablet in front of experimenter; No age effect Behavior 1.5−7, n = 42 Oberman et al, 2008 Action observation Mu (8−13 Hz) for familiar and stranger hand actions EEG 8−12, n = 13 * Oberman et al, 2013 Action observation Mu suppression during observation (not execution) gets stronger with age EEG 6−17, n = 51 * Ohnishi et al, 2004 Action observation Same network as observed in adult studies fMRI 7−10, n = 11 O’Sullivan et al, 2018 Automatic imitation Correct movement and reaction time effects (live). No age effect Behavior 3−7, n = 72 * Rabinowitch and Knafo-Noam, 2015 Synchrony Child-child synchronous rhythmic interaction increases feeling of closeness Behavior 8−9, n = 148 * Rabinowitch and Meltzoff, 2017a Synchrony Synchronous and asynchronous sway increase sharing Behavior 4, n = 162 * Rabinowitch and Meltzoff, 2017b Syn...…”
Section: Scope Definitions and Why Study Interpersonal Motor Alignmementioning
confidence: 99%
See 1 more Smart Citation
“…Less activation anterior parietal fMRI 7−10, n = 21 Nishimura et al, 2018 Action observation Mu suppression during observation weaker than in adults and less in allocentric compared to egocentric configuration EEG 8−12, n = 28 Nobusako et al, 2018 Automatic imitation Effect of congruency on trajectory when drawing on tablet in front of experimenter; No age effect Behavior 1.5−7, n = 42 Oberman et al, 2008 Action observation Mu (8−13 Hz) for familiar and stranger hand actions EEG 8−12, n = 13 * Oberman et al, 2013 Action observation Mu suppression during observation (not execution) gets stronger with age EEG 6−17, n = 51 * Ohnishi et al, 2004 Action observation Same network as observed in adult studies fMRI 7−10, n = 11 O’Sullivan et al, 2018 Automatic imitation Correct movement and reaction time effects (live). No age effect Behavior 3−7, n = 72 * Rabinowitch and Knafo-Noam, 2015 Synchrony Child-child synchronous rhythmic interaction increases feeling of closeness Behavior 8−9, n = 148 * Rabinowitch and Meltzoff, 2017a Synchrony Synchronous and asynchronous sway increase sharing Behavior 4, n = 162 * Rabinowitch and Meltzoff, 2017b Syn...…”
Section: Scope Definitions and Why Study Interpersonal Motor Alignmementioning
confidence: 99%
“…In four-year-old children, synchronous interactions of only three minutes may already lead to enhanced peer cooperation. In children of eight to nine years of age they enhance closeness and feelings of similarity ( Rabinowitch and Knafo-Noam, 2015 ; Rabinowitch and Meltzoff, 2017a ). These positive effects extend from synchrony in direct interaction to joint music making and rhythmic synchrony.…”
Section: Investigation Of Interpersonal Motor Alignment Its Positivementioning
confidence: 99%
“…The positive impact of music on social skills has been demonstrated beyond ASD 21 , 22 . Typically developing children are more likely to play with another following a shared musical experience 23 and joint musical interactions can enhance emotional empathy, prosociality and bonding in children 24 26 . More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory 27 31 , thus allowing transfer of music-related therapeutic effects to non-musical domains 32 through structural and functional brain changes 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically-developing children are more likely to play with another following a shared musical experience (39) and joint musical interactions can enhance emotional empathy, prosociality and bonding in children (40)(41)(42) and adults (43)(44)(45)(46). More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory (47)(48)(49), thus allowing transfer of music-related therapeutic effects to non-musical domains (50-54) through structural and functional brain changes (55)(56)(57)(58).…”
Section: Introductionmentioning
confidence: 99%